GIS-material for the archaeological project: Settlement remains by the burial ground in Sund - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to construction of an electric main system within the properties Sund 1:3 and 4:16, Fivelstad parish, Motala municipality, the Swedish National Heritage Board's contract archaeology division, UV Öst, performed a preliminary investigation/an antiquarian inspection along the cable trench. Approx. 30 m from the trench is a burial ground, RAÄ 7. No new graves were found around the burial ground, but c. 100 m to the north-west two hearths and a post hole were discovered, probably being part of a settlement. The hearths were of typical early Iron Age character and thus fit into the burial ground context. The remains probably extend in a north-south direction, and UV Öst considers it safe for the cable to be laid as planned, except for in the area where the remains were found.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the antiquarian inspection was to elucidate whether any archaeological remains were going to be affected by the trenching.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför nybyggnad av ledningsnät inom fastigheterna Sund 1:3 och 4:16, Fivelstads socken, Motala kommun, utförde Riksantikvarieämbetet UV Öst en arkeologisk förundersökning i form av antikvarisk kontroll utmed ledningssträckan. Ett 30-tal meter ifrån ledningssträckan finns ett registrerat gravfält, RAÄ 7. Närmast gravfältet påträffades inga ytterligare gravanläggingar men ca 100 m NV om gravfältet påträffades två härdar och ett stolphål som förmodas höra till en boplats. Härdarna var av typisk äldre järnålderskaraktär varför de passar bra in i sammanhanget med gravfältet. Lämningarna uppfattades som förhållandevis begränsade och dess utbredning löper sannolikt i N-S riktning varför UV Öst föreslog att ledningen kunde förläggas som planerat med undantag för där lämningarna påträffades.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den antikvariska kontrollen var att klargöra om arkeologiska lämningar påverkades av schaktningsarbetet.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Boplatslämningar vid gravfältet i Sund
Keywords: Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi